The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10816-015-9258-7
|View full text |Cite
|
Sign up to set email alerts
|

Design Space and Cultural Transmission: Case Studies from Paleoindian Eastern North America

Abstract: Tool design is a cultural trait-a term long used in anthropology as a unit of transmittable information that encodes particular behavioral characteristics of individuals or groups. After they are transmitted, cultural traits serve as units of replication in that they can be modified as part of a cultural repertoire through processes such as recombination, loss, or partial alteration. Artifacts and other components of the archaeological record serve as proxies for studying the transmission (and modification) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 231 publications
(239 reference statements)
0
21
0
Order By: Relevance
“…This phenomenon occurs in other aspects of culture as well. In a study of projectile points from eastern North America that immediately postdate Clovis, including a large sample from the northeast, Gingerich et al 74 found increasing variation in bifacial flake-scar symmetry, which was not the case in the Clovis-only study of Sholts et al 47 The resulting regionalization in the east 31,42,71,73,113,118 shows up in morphologically distinct, fully fluted, basally thinned, and unfluted forms, with subregional variants, including types such as Barnes, Beaver Lake, Bull Brook, Crowfield, Cumberland, Dalton, Debert/Vail, Quad, Redstone, San Patrice, Suwannee, Simpson, and some lanceolate shapes that resemble points from the Great Plains. In contrast, design and manufacture in the east were tied to two tiers of social learning, one tied to conformist transmission of ancestral tool-making processes-flake removal-and the other a product of drift and, perhaps to some extent, regional adaptation-shape.…”
Section: Social and Individual Learning In The Eastmentioning
confidence: 99%
See 4 more Smart Citations
“…This phenomenon occurs in other aspects of culture as well. In a study of projectile points from eastern North America that immediately postdate Clovis, including a large sample from the northeast, Gingerich et al 74 found increasing variation in bifacial flake-scar symmetry, which was not the case in the Clovis-only study of Sholts et al 47 The resulting regionalization in the east 31,42,71,73,113,118 shows up in morphologically distinct, fully fluted, basally thinned, and unfluted forms, with subregional variants, including types such as Barnes, Beaver Lake, Bull Brook, Crowfield, Cumberland, Dalton, Debert/Vail, Quad, Redstone, San Patrice, Suwannee, Simpson, and some lanceolate shapes that resemble points from the Great Plains. In contrast, design and manufacture in the east were tied to two tiers of social learning, one tied to conformist transmission of ancestral tool-making processes-flake removal-and the other a product of drift and, perhaps to some extent, regional adaptation-shape.…”
Section: Social and Individual Learning In The Eastmentioning
confidence: 99%
“…The dichotomous intraregional results from the upper midwest strongly suggest that Clovis foragers engaged in two tiers of social learning. 71 The lower, ancestral tier relates to point production and can be tied to conformist transmission of ancestral tool-making processes across the larger North American Clovis population. 47 In other words, dispersing Clovis groups were still socially connected across large regions of North America and directly transmitting technological knowledge to each other, resulting in low interregional variation in how points were being flaked.…”
Section: Social and Individual Learning In The Eastmentioning
confidence: 99%
See 3 more Smart Citations